(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
Effective domestic or household waste management is crucial for environmental sustainability and public health. Improper disposal practices lead to adverse sanitation, pollution, disease outbreaks and ecosystem degradation. This study examines waste disposal practices and awareness level among the households in a selected village in Tiswadi taluka of Goa. While residents show high awareness of the harmful effects of improper waste management, a significant gap exists between knowledge and action. Factors such as poor recycling habits, lack of infrastructure for waste disposal and limited public education contribute to this issue. By analysing household behaviours and perceptions, the study aims to recommend strategies for improving waste management practices and enhancing community health and sustainability. Improper waste disposal continues to pose significant environmental and public health challenges contributing to pollution, fear of disease outbreaks and the degradation of ecosystems. This study evaluates household waste management practices, awareness levels, and perceptions among 60 respondents from a selected village. Data collection was facilitated through structured questionnaires and findings were analysed using tables and visualized through pie charts created in Microsoft Excel to better understand patterns and trends. A majority of respondents reported suffering from allergies due to waste exposure, and many experienced infectious diseases, highlighting immediate health threats stemming from poor waste management. The study also found that while several respondents consistently separated waste, a considerable number displayed inconsistent segregation practices. Daily waste disposal was commonly observed among households, reflecting regular management efforts; however, recycling habits remained poor, with most respondents rarely recycling and none reporting frequent recycling. Many individuals reused plastic bags, which is a positive trend, yet harmful practices like burning plastic and dumping in water bodies still persist among a minority. The findings suggest that there is lack of confidence in local government initiatives and poor recycling support. The study recommends strengthening institutional waste management support, expanding public education initiatives focused on sanitary and household waste disposal, improving waste segregation facilities and promoting community engagement to bridge the gap between knowledge and practice. Addressing these issues is crucial to ensuring sustainable development in the studied communities.